Uji Kelayakan Perangkat Pembelajaran Model Inkuiri Berbasis Kearifan Lokal Aceh Besar pada Materi Sistem Pencernaan dan Nutrisi Seimbang di Kelas V SD/MI - Daniah Daniah (Politeknik Kampar, 2024)
MIN 20 Aceh Besar is one of the state schools in the science learning process using package books in the form of teacher's books and student learning books provided by the government, which is a publication outside the Aceh region, where the package book itself does not discuss the local wisdom that exists in Aceh, especially in Aceh Besar so that students still do not understand the meaning and examples of local wisdom that exist in the local area, namely Aceh Besar. The teacher delivers material according to the textbook without using learning models, especially science material. The aim of the research is to analyze the feasibility test of an inquiry model learning device based on Aceh Besar's local wisdom on material on the digestive system and balanced nutrition that is appropriate for class V students of MIN 20 Aceh Besar. This research uses the Research and Development (R&D) method with the ADDIE model. The data collection technique uses a feasibility test sheet. The data analysis technique uses a percentage formula. The research results of the feasibility test of the learning device based on local wisdom, Aceh Besar obtained a result of 98.3% with a very feasible category, the results of the feasibility test on the digestive system material and balanced nutrition with a model of inquiry based on local wisdom, Aceh Besar obtained a result of 94% with a very feasible category and The results of the language feasibility test on local wisdom-based inquiry learning tools, Aceh Besar, obtained 80% results with adequate national education. Based on the results of the research, it can be concluded that the feasibility test of the Aceh Besar local wisdom-based inquiry model learning device on digestive system and balanced nutrition material is suitable for use in the learning process.